Clinical and genetic characterization of pediatric patients with Wilson’s disease from Yunnan province where ethnic minorities gather - Wang, Yanjun; Fang, Jiahui; Li, Bin; Li, Chongyang; Liu, Shan; He, Juan; Tao, Lvyan; Li, Cuifen; Yang, Ya; Li, Li; Xiao, Shufang (Frontiers in Genetics, 2023)
Background: Wilson's disease (WD) is an autosomal recessive genetic disease caused by ATP7B (encoding a copper-transporting P-type ATPase) mutations，which has a low prevalence and characterized by a copper metabolism disorder. WD shows various characteristics according to race and geographical region. This study was aimed to discover the novel ATP7B mutations in pediatric patients with WD from Yunnan Province where ethnic minorities gather and provide a comprehensive analysis of ATP7B mutations in different ethnic groups of Southwest China. Methods: A total 45 patients from 44 unrelated families were recruited who were clinically diagnosed with WD. Routine clinical examination and laboratory evaluation were performed and information of age, gender, ethnic group and symptoms at onset were collected. Direct sequencing of the ATP7B gene was performed in 39 of the 45 patients and their families. Results: In this study, participants came from 7 different ethnic groups in China: Han, Bai, Dai, Zhuang, Yi, Hui and Jingpo. Just 3/10 patients from ethnic minorities presented with elevated transaminases, compared to the majority of ethnic Han patients who had them. 40 distinct mutations (28 missense, 6 splicing, 3 nonsense, 2 frameshift, and 1 mutation of uncertain significance) in 39 patients with WD were identified. Of these, 4 novel mutations were found. The most frequent mutation was c.2333G > T (p.R778L, allelic frequency: 15.38%). According to phenotype-genotype correlation analysis, patients from ethnic minorities were more likely than Han patients to have homozygous mutations (p=0.035). The patients carrying the c.2310C > G had a lower serum ceruloplasmin levels (p=0.012). In patients with heterozygous mutations, c.3809A > G was significantly associated with ethnic minorities (p=0.042). The frequency of protein-truncating variant (PTV) in patients from Han was 34.38% (11/32), while we didn’t even find a single PTV in patients from ethnic minorities. Conclusion: This study revealed genetic defects of 39 pediatric patients with WD from Yunnan Province where ethnic minorities gather, and identified four novel mutations which have enriched the WD database. More importantly, we charactered the genotype and phenotype in different minorities which could enhance the current knowledge about the population genetics of WD in China.